A Church That Can and Cannot Change: The Dynamics of Tradition. (June 2015) - Sanks, T. Howland
After reviewing some previous contributions to the discussion of continuity and change in the Christian tradition, the article suggests another way of thinking about the problem by using Pierre Bourdieu's analytic notion of habitus .